Annulus Fibrosus Can Strip Hyaline Cartilage End Plate from Subchondral Bone: A Study of the Intervertebral Disk in Tension. (October 2015) - Balkovec, Christian; Adams, Michael A.; Dolan, Patricia; McGill, Stuart M.
Study Design: Biomechanical study on cadaveric spines. Objective: Spinal bending causes the annulus to pull vertically (axially) on the end plate, but failure mechanisms in response to this type of loading are poorly understood. Therefore, the objective of this study was to identify the weak point of the intervertebral disk in tension. Methods: Cadaveric motion segments (aged 79 to 88 years) were dissected to create midsagittal blocks of tissue, with ∼10 mm of bone superior and inferior to the disk. From these blocks, 14 bone–disk–bone slices (average 4.8 mm thick) were cut in the frontal plane. Each slice was gripped by its bony ends and stretched to failure at 1 mm/s. Mode of failure was recorded using a digital camera. Results: Of the 14 slices, 10 failed by the hyaline cartilage being peeled off the subchondral bone, with the failure starting opposite the lateral annulus and proceeding medially. Two slices failed by rupturing of the trabecular bone, and a further two failed in the annulus. Conclusions: The hyaline cartilage–bone junction is the disk's weak link in tension. These findings provide a plausible mechanism for the appearance of bone and cartilage fragments in herniated material. Stripping cartilage from the bony end plate would result in the herniated mass containing relatively stiff cartilage that does not easily resorb.